Assessment of mechanical and fatigue crack growth properties of wire + arc additively manufactured mild steel components. Issue 10 (20th July 2022) - Shamir, Muhammad; Igwemezie, Victor; Lotfian, Saeid; Jones, Rhys; Asif, Huzaifa; Ganguly, Supriyo; Mehmanparast, Ali
Abstract: A study has been conducted to evaluate the mechanical and fatigue crack propagation properties of wire + arc additively manufactured ER70S‐6 components. A parallel‐built deposition strategy was employed to fabricate the additively manufactured wall. The hardness values were slightly higher at the bottom and top of the wall due to the presence of Widmanstätten ferrite and carbides. The characterization of mechanical properties in both orientations; parallel and perpendicular to the deposition direction showed a marginal difference in yield strength and ultimate tensile strength. The crack growth rates were correlated with linear elastic fracture mechanics parameter Δ K and compared with an oscillation‐built deposition strategy from the literature. The crack growth rates of both deposition strategies were found to be very similar to each other. Furthermore, it has been demonstrated that the variability in the crack growth histories can be reasonably well captured by using the NASGRO crack growth equation.